2022
DOI: 10.1002/ijc.33913
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone receptor isoform ratio dictates antiprogestin/progestin effects on breast cancer growth and metastases: A role for NDRG1

Abstract: Progesterone receptors (PRs) ligands are being tested in luminal breast cancer. There are mainly two PR isoforms, PRA and PRB, and their ratio (PRA/PRB) may be predictive of antiprogestin response. Our aim was to investigate: the impact of the PR isoform ratio on metastatic behaviour, the PR isoform ratio in paired primary tumours and lymph node metastases (LNM) and, the effect of antiprogestin/progestins on metastatic growth. Using murine and human metastatic models, we demonstrated that tumours with PRB > PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…In HIR tumors, the lowest GPC levels (within the tumors) again seems to reflect a distinct status of membrane metabolism where lower GPC may be the result of higher phospholipid (phosphatidylcholine, main membrane constituent) synthesis. Again, potentially different metastatic status may relate to the signature differences described above, although such feature could not be evaluated for HIR tumors, due to their rapid growth and subsequent early sacrifice of the animals (before metastasis could occur or be detected) ( 76 ). This possible relationship between metabolite signatures and tumor metastatic status is of large interest in BC research and requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In HIR tumors, the lowest GPC levels (within the tumors) again seems to reflect a distinct status of membrane metabolism where lower GPC may be the result of higher phospholipid (phosphatidylcholine, main membrane constituent) synthesis. Again, potentially different metastatic status may relate to the signature differences described above, although such feature could not be evaluated for HIR tumors, due to their rapid growth and subsequent early sacrifice of the animals (before metastasis could occur or be detected) ( 76 ). This possible relationship between metabolite signatures and tumor metastatic status is of large interest in BC research and requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Aromatase inhibitors or ER degraders may not work together with mifepristone, because they inhibit PR expression. Because we have already shown that lymph node metastases maintain the same PR isoform ratio as the primary tumor ( 15 ), it may be speculated that this treatment might prove suitable in an adjuvant setting, or alternatively, in a neoadjuvant setting, if further immunotherapy is suggested. Ongoing studies are currently evaluating the combination of mifepristone and CDK4/6 inhibitors in preclinical PRA-H models.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in vitro , mifepristone exerts antiproliferative effects only in PRA-H+ cells ( 16 ), suggesting that the direct antiprogestin effect of mifepristone is the prevailing effect, without ruling out a contribution from its antiglucocorticoid or its antiandrogenic effects (reviewed in ref. 15 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ratio of the two PR isoforms, PR-A and PR-B, may be predictive for progestin and antiprogestin response. Breast cancers with high PR-A/PR-B ratios metastatic growth was inhibited by antiprogestins, and the metastatic growth of breast cancers with low PR-A/PR-B ratios was inhibited with progestins [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%